Sulforaphane: A nutraceutical against diabetes-related complications - Sinenhlanhla X.H. Mthembu; Sithandiwe E. Mazibuko-Mbeje; Marakiya T. Moetlediwa; Ndivhuwo Muvhulawa; Sonia Silvestri; Patrick Orlando; Bongani B. Nkambule; Christo J.F. Muller; Duduzile Ndwandwe; Albertus K. Basson; Luca Tiano; Phiwayinkosi V. Dludla (Elsevier, 2023)
There is an increasing interest in the use of nutraceuticals and plant-derived bioactive compounds from foods for their potential health benefits. For example, as a major active ingredient found from cruciferous vegetables like broccoli, there has been growing interest in understanding the therapeutic effects of sulforaphane against diverse metabolic complications. The past decade has seen an extensive growth in literature reporting on the potential health benefits of sulforaphane to neutralize pathological consequences of oxidative stress and inflammation, which may be essential in protecting against diabetes-related complications. In fact, preclinical evidence summarized within this review supports an active role of sulforaphane in activating nuclear factor erythroid 2-related factor 2 or effectively modulating AMP-activated protein kinase to protect against diabetic complications, including diabetic cardiomyopathy, diabetic neuropathy, diabetic nephropathy, as well as other metabolic complications involving non-alcoholic fatty liver disease and skeletal muscle insulin resistance. With clinical evidence suggesting that foods rich in sulforaphane like broccoli can improve the metabolic status and lower cardiovascular disease risk by reducing biomarkers of oxidative stress and inflammation in patients with type 2 diabetes. This information remains essential in determining the therapeutic value of sulforaphane or its potential use as a nutraceutical to manage diabetes and its related complications. Finally, this review discusses essential information on the bioavailability profile of sulforaphane, while also covering information on the pathological consequences of oxidative stress and inflammation that drive the development and progression of diabetes.